Inclusive Education as a Democratic Challenge-Ambivalences of Communities in Contexts of Power - Meike Kricke; Stefan Neubert (MDPI AG, 2017)
Our essay is keyed to the second and fourth chapter of Dewey's Democracy and Education. We start by looking at education as a social function and close with education as growth. References will be made to other writings of Dewey's, especially from the later works. We connect Dewey's classical approach with inclusion as a feature of contemporary debates in educational theory and practice. Within this frame, we also draw critical connections to selected perspectives from Michel Foucault and Zygmunt Bauman. The aim is twofold: First, we wish to show the lasting relevance of Dewey's approach in and for our time. Second, we intend to invite some perspectives for reconstructing the Deweyan tradition in accordance with more recent developments and challenges, including the ambivalences of communities in modernity, especially in times of liquid modernity as described by Bauman.